2017
DOI: 10.20409/berj.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Image of Conflict-ridden Destinations: An EEG and Eye Tracker Analysis

Abstract: This study aims to investigate the perceived images of Eastern and Southeastern Anatolia regions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 88 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…The validity and reliability of research are associated with the number of data collection methods (Bogdan and Biklen, 2006;Koç and Boz, 2014b;Taşkın et al, 2017). According to the Koc and Boz (2014b) study, the use of triangulation in the data collection method is crucial to the validity, reliability and generalizability of the data.…”
Section: The Methodsmentioning
confidence: 99%
“…The validity and reliability of research are associated with the number of data collection methods (Bogdan and Biklen, 2006;Koç and Boz, 2014b;Taşkın et al, 2017). According to the Koc and Boz (2014b) study, the use of triangulation in the data collection method is crucial to the validity, reliability and generalizability of the data.…”
Section: The Methodsmentioning
confidence: 99%
“…For example, whilst people generally pay strongest attention to visual cues [44,45], EEG and eye-tracking analyses found that in conflict-ridden destinations, risk-motivated tourists shift their attention to verbal cues [46]. The combination of EEG and eye tracking is also valuable in understanding tourists' perceptions, attitudes, and responses to service atmospherics [47].…”
Section: Opportunities For Psychophysiological Approachesmentioning
confidence: 99%
“…Concerning the masculinity, Turkey has a soft score, 45, in contrast to the commonly highlighted features of the Turkish culture, such as patriarchy and women's roles in family rather than workplace, by different researchers (e.g., Hisrich and Öztürk, 1999;Kalafatoglu and Mendoza, 2017). For the uncertainty avoidance, the score of 85 demonstrates that the Turkish culture tends to use rituals in order to avoid ambiguities and, as such is against the inherent risk-taking feature of entrepreneurship, as Taşkın et al (2017) pointed out. Finally, Turkey receives intermediate scores both for the dimension of long-term orientation (46), which shows that it is in-between the normative and the pragmatic society, and for the indulgence (49), which indicates that it is regarded as neither indulgent nor restrained.…”
Section: The Turkish Contextmentioning
confidence: 99%